[Letter-books of St Joseph's Industrial School] - St. Joseph's Industrial School (Calgary, Alta.); Canada Dept. of Indian Affairs; Glenbow Museum; Adam Matthew Digital (Adam Matthew Digital, 1884)
Correspondence files of St. Joseph's Industrial School, collated in 6 monthly increments. The files contain letters to the Dept. of Indian Affairs regarding the running of the school and the education and work of the pupils